DEFINITIONS OF INFORMATION: ANALYSIS OF ACADEMIC WORKS (World Bulletin of Management and Law, 2022)
This article examines the essence of the concept of information security, opinions, approaches of scientists regarding this concept. As a result, a practical proposal is given regarding the formulation of this concept in a new form
Keywords: information security; opinion; scientists; status